A novel intrinsically disordered outer membrane lipoprotein of Aggregatibacter actinomycetemcomitans binds various cytokines and plays a role in biofilm response to interleukin-1β and interleukin-8 - Tuuli Ahlstrand; Heidi Tuominen; Arzu Beklen; Annamari Torittu; Jan Oscarsson; Raija Sormunen; Marja T. Pöllänen; Perttu Permi; Riikka Ihalin (Taylor & Francis, 2022)
Intrinsically disordered proteins (IDPs) do not have a well-defined and stable three-dimensional fold. Some IDPs can function as either transient or permanent binders of other proteins and may interact with an array of ligands by adopting different conformations. A novel outer membrane lipoprotein, bacterial interleukin receptor I (BilRI) of the opportunistic oral pathogen Aggregatibacter actinomycetemcomitans binds a key gatekeeper proinflammatory cytokine interleukin (IL)-1β. Because the amino acid sequence of the novel lipoprotein resembles that of fibrinogen binder A of Haemophilus ducreyi, BilRI could have the potential to bind other proteins, such as host matrix proteins. However, from the tested host matrix proteins, BilRI interacted with neither collagen nor fibrinogen. Instead, the recombinant non-lipidated BilRI, which was intrinsically disordered, bound various pro/anti-inflammatory cytokines, such as IL-8, tumour necrosis factor (TNF)-α, interferon (IFN)-γ and IL-10. Moreover, BilRI played a role in the in vitro sensing of IL-1β and IL-8 because low concentrations of cytokines did not decrease the amount of extracellular DNA in the matrix of bilRI- mutant biofilm as they did in the matrix of wild-type biofilm when the biofilms were exposed to recombinant cytokines for 22 hours. BilRI played a role in the internalization of IL-1β in the gingival model system but did not affect either IL-8 or IL-6 uptake. However, bilRI deletion did not entirely prevent IL-1β internalization, and the binding of cytokines to BilRI was relatively weak. Thus, BilRI might sequester cytokines on the surface of A. actinomycetemcomitans to facilitate the internalization process in low local cytokine concentrations.